Uptake of bacteria by trophozoites of Giardia duodenalis (Say) - Sogayar, M. I L; Gregorio, E. A. (My University, 1989)
Rod-like bacteria were found in the cytoplasm of trophozoites of Giardia duodenalis (Say) in domestic rats (Rattus rattus). These structures were always in phagocytic vacuoles without signs of bacteria digestion or degradation of the trophozoite cytoplasm. The uptake of the bacteria was observed from their attachment to the trophozoite membrane until their total incorporation by phagocytosis.
Keywords: animal cell; giardia lamblia; nonhuman; phagocytosis; protozoon; trophozoite; ultrastructure; Animal; Bacteria; Giardia; Microscopy, Electron; Phagocytosis; Rats; Support, Non-U.S. Gov't; Vacuoles